Correction: Shaikh et al. A Review of Artificial Intelligence-Based Down Syndrome Detection Techniques. Life 2025, 15, 390 - Mujeeb Ahmed Shaikh; Hazim Saleh Al-Rawashdeh; Abdul Rahaman Wahab Sait (Life, 2025)
Additional Affiliation [...]